Analysis of the Influence of Tax Knowledge, e-Filing Tax System, Tax Authority Services, and Tax Law Enforcement on Tax Awareness through Taxpayer Compliance - Sri Rusiyati (Green Publisher, 2025)
The purpose of this study is to determine the extent of the influence of tax knowledge, the e-filing tax system, tax authority services, and tax law enforcement on tax awareness and taxpayer compliance, both directly and indirectly. The population in this study was 252,953 SMEs in East Jakarta. Based on this number, the sample for this study consists of 124 taxpayers from small and medium enterprises (SMEs) in East Jakarta. The population in this study is taxpayers from small and medium enterprises (SMEs) in East Jakarta. Sampling was conducted using purposive sampling. The purposive sampling used in this study is judgment sampling, which is the selection of samples based on the fact that the samples or respondents are considered the primary source of information capable of providing the necessary information. The researcher will distribute questionnaires to the accounting and taxation divisions working in the companies. For reasons of data adequacy in the Structural Equation Model (SEM) analysis, at least 200 samples are required. The unit of analysis in this study is the individual or employee who handles SME taxes. This study uses primary data sources from individual respondents. The results of this study are as follows: 1) Tax Knowledge has a positive and significant effect on Brand Awareness among SMEs in East Jakarta; 2) E-Filing Tax System has a positive and significant effect on Brand Awareness among SMEs in East Jakarta; 3) Tax Authority Services have a positive and significant effect on Brand Awareness among SMEs in East Jakarta; 4) Tax Law Enforcement has a positive and significant effect on Brand Awareness among SMEs in East Jakarta; 5) Tax Knowledge has a positive and significant effect on Tax Compliance among SMEs in East Jakarta; 6) E-Filing Tax System has a positive and significant effect on Tax Compliance among SMEs in East Jakarta; 7) Tax Authority Services have a positive and significant effect on Tax Compliance among SMEs in East Jakarta; 8) Tax Law Enforcement has a positive and significant effect on Tax Compliance among SMEs in East Jakarta; 9) Brand Awareness has a positive and significant effect on Tax Compliance among SMEs in East Jakarta; 10) Tax knowledge has a positive and significant effect on Taxpayer Compliance mediated by Tax Awareness among SMEs in East Jakarta; 11) The E-Filing Tax System does not have a positive and significant effect on Taxpayer Compliance mediated by Tax Awareness among SMEs in East Jakarta; 12) Tax Authority Service positively and significantly influences Tax Compliance mediated by Tax Awareness among SMEs in East Jakarta; and 13) Tax Law Enforcement does not positively and significantly influence Tax Compliance mediated by Tax Awareness among SMEs in East Jakarta.